2013
DOI: 10.1371/journal.pone.0082121
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsic Propensity of Murine Peritoneal B1b Cells to Switch to IgA in Presence of TGF-β and Retinoic Acid

Abstract: AimsIn the present study we have investigated the comparative switching propensity of murine peritoneal and splenic B cell subpopulations to IgA in presence of retinoic acid (RA) and TGF-β.Methods and ResultsTo study the influence of RA and TGF-β on switching of B cell subpopulations to IgA, peritoneal (B1a, B1b and B2 cells) and splenic (B1a, marginal zone, and B2) B cells from normal BALB/c mice were FACS purified, cultured for 4 days in presence of RA and TGF-β and the number of IgA producing cells was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…However, we found no differences in IgE + B cells of Lgals3 +/+ and Lgals3 −/− mice (data not shown). As peritoneal B cells are committed to an IgA repertoire (Roy et al 2013) and as high levels of IgA are found in the serum during schistosomiasis (Gaber et al 2010), we monitored sIgA expression by peritoneal B cells and conclude that a significant correlation exists between galectin-3 and IgA + differentiating plasma cells in the peritoneal cavity. Kracker and colleagues demonstrated that IgA/IgM co-expression is a remarkable event in the course of immunoglobulin class switching (Kracker and Durandy 2011) and our data indicate that galectin-3 is a potent regulator of IgA expression on B1 cells during chronic schistosomiasis and cytokine induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found no differences in IgE + B cells of Lgals3 +/+ and Lgals3 −/− mice (data not shown). As peritoneal B cells are committed to an IgA repertoire (Roy et al 2013) and as high levels of IgA are found in the serum during schistosomiasis (Gaber et al 2010), we monitored sIgA expression by peritoneal B cells and conclude that a significant correlation exists between galectin-3 and IgA + differentiating plasma cells in the peritoneal cavity. Kracker and colleagues demonstrated that IgA/IgM co-expression is a remarkable event in the course of immunoglobulin class switching (Kracker and Durandy 2011) and our data indicate that galectin-3 is a potent regulator of IgA expression on B1 cells during chronic schistosomiasis and cytokine induction.…”
Section: Discussionmentioning
confidence: 99%
“…*P<0.05 Peritoneal B1 lymphocytes express IL-5R constitutively (Hitoshi et al 1990) and higher levels of IL-5 in Lgals3 −/− mice (Oliveira et al 2009) and promptly synthesize IgA (Takatsu et al 2009). On the other hand, peritoneal B1 cells switch more readily to IgA than do splenic follicular or peritoneal B2 cells after B lymphocyte stimulator/lipopolysaccharide/TGF-β in vitro (Kaminski and Stavnezer 2006) and specifically, peritoneal B1b cells switch to IgA under the influence of the synergistic effect of TGF-β and retinoic acid (Roy et al 2013). Indeed, we have arguments to suggest that galectin-3 plays a regulatory role on IgA + cell differentiation controlling IL-5 and TGF-β functions in the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of our study is that the population of B1a cells has been measured in peripheral blood and not in the intestinal mucosa. However, Roy et al [43] observed a considerable high propensity of murine splenic B1a cells to switch to IgA.…”
Section: Discussionmentioning
confidence: 99%
“…In human B cells, RA increased IgA production and the expression of germ-line IgA1 and IgA2 transcripts (GLTa1 and GLTa2), and under the same conditions, RA did not increase IgM and IgG productions [41] . RA also plays a vital role together with TGF-β in the presence of Runx proteins on switching of different B cell subpopulations to IgA [42,43] . Yet no one focused on the role of RA in IgA CSR in IgAN.…”
Section: Discussionmentioning
confidence: 99%